Collaboration Scripts as Scaffolds: Enhancing Regulatory Processes and Socio-emotional Dynamics in Ensemble Rehearsals - Tahirbegi, Damla; Järvenoja, Hanna (Music & science, 2025)
This study aims to enhance socio-emotional awareness and regulatory processes in small ensemble rehearsals through the design and implementation of a macro-level collaboration script. Developed using design-based research principles, the script is grounded in the cyclical model of regulated learning ( Hadwin et al., 2018 ; Zimmerman & Campillo, 2003 ) and incorporates prompts adapted from Näykki et al. (2017) for ensemble contexts. Five student ensembles from a higher music education institution in Norway participated in the study. Ensembles using the script (n = 3) were compared with baseline ensembles without it (n = 2). Data from video recordings and focus group discussions were analyzed using qualitative content analysis. The findings indicate that the script effectively supports socially shared regulation of learning by fostering collaborative planning, shared task and emotional monitoring, and reflective dialogue. Scripted ensembles consistently engaged in all regulated learning phases (planning, monitoring, and reflection) and exhibited greater socio-emotional awareness through more equitable participation. Notably, both conditions spent less than half of the rehearsal time on actual performance, highlighting the central role of verbal interaction in ensemble rehearsals. These findings suggest the collaboration script serves as an effective scaffold for enhancing socio-emotional dynamics and group-level regulation, offering valuable insights for improving student-led ensemble rehearsals. Further research is needed, however, to refine its design, particularly in balancing structured guidance with the fluid, creative dynamics essential to musical collaborations.